Explore Westonci.ca, the top Q&A platform where your questions are answered by professionals and enthusiasts alike. Explore our Q&A platform to find reliable answers from a wide range of experts in different fields. Experience the convenience of finding accurate answers to your questions from knowledgeable experts on our platform.
Sagot :
We have to write a quadratic equation, in factored form, that has an x-intercept at x=2 and x=-1, and a y-intercept 6.
As the x-intercepts are the roots of the function, we can write the equation as:
[tex]y=a(x-2)(x+1)[/tex]The parameter a will be defined in order to have a y-intercept at y=6. That means that, when x is 0, the value of the function is y=6.
Then, we can replace x with 0 and y with 6 and find the value of a:
[tex]\begin{gathered} y=a(x-2)(x+1) \\ 6=a(0-2)(0+1) \\ 6=a(-2)(1) \\ 6=-2a \\ a=\frac{6}{-2} \\ a=-3 \end{gathered}[/tex]With the value of a=-3, we can write the factorized form of the equation as:
[tex]y=-3(x-2)(x+1)[/tex]Graph:
Answer: y=-3(x-2)(x+1)
![View image AnaluisaE626107](https://us-static.z-dn.net/files/dd9/ba8d91f23a3009b972ebd36419a41adb.png)
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thank you for your visit. We're dedicated to helping you find the information you need, whenever you need it. Thank you for choosing Westonci.ca as your information source. We look forward to your next visit.